Répartition spatiale des trypanosomoses animales en relation avec la chimiorésistance dans la zone cotonnière de l’Afrique de l’Ouest (Mali et Guinée) - Talaki, E.; Sidibe, I.; Diall, O.; Grace, Delia; Barry, A.M.; Djiteye, A.; Bocoum, Z.; Clausen, Peter-Henning; Randolph, Thomas F.; Affognon, Hippolyte D.; Hendrickx, G.; Pangui, L.J.; et al. (2006)
Cross sectional surveys (2002-2004) achieved in 89 villages, carried on 5474 cattle and 1908 tse tse flies (G. palpalis: 53%; G. tachinoides: 45% and G. morsitans: 2%) have been captured. Following these investigations, several suspected villages have been chosen for longitudinal surveys in order to put out the failures of treatments to the trypanocides (isometamidium chloride and diminazene aceturate) on cattle. The spatial analysis of the results shows heterogeneity in the distribution. The size of the phenomenon decreases from the East to the West of the zone. In Mali, the average parasitological prevalence is 4.5% for a peak value of 22% against an average prevalence of 2.8% for a peak value of 11.7% in Guinea. The infections in Mali are caused by T. congolense (49%) and T. vivax (51%). Those of Guinea are characterized by the predominance of T. brucei (59%) followed of T. congolense (36%) and T. vivax (5%). On the entomological plan, one notices the absence of G. morsitans in the East part in Mali, but in Guinea it is G. tachinoides who is absent. Different levels of chemoresistance have been identified in the zone.